Van der Valk. Season 3 [videorecording (DVD)] - Murray, Chris (Screenwriter) (PBS Distribution, 2023)
For Commisaris Piet van der Valk, it's a new day and a new dawn as he welcomes two new Sergeants to the team, the hotshot but impulsive Eddie Suleman and the technical whiz Citra Li.